2004
DOI: 10.1073/pnas.0406066101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic antagonism between RNA-binding protein CUGBP2 and cyclooxygenase-2-mediated prostaglandin E 2 in radiation damage

Abstract: Damage to intestinal epithelium limits the use of ionizing radiation (IR) in cancer therapy. Prostaglandins (PGs), generated through the action of cyclooxygenase-1 (COX-1) and COX-2 protect the intestinal stem cells from IR. In previous studies, we demonstrated that the RNA-binding protein CUGBP2 regulates the stability and translation of COX-2 mRNA by interacting with AU-rich sequences in 3 UTR. Here, we demonstrate a dynamic antagonistic relationship between CUGBP2 and COX-2. Both CUGBP2 and COX-2 are rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
5
33
0
1
Order By: Relevance
“…Similar findings were reported in other recent studies investigating COX-2 expression in the mouse (25) and in porcine intestinal tissue (3). Furthermore, Murmu et al have demonstrated that not only the COX-2 protein band but also the mRNA for COX-2 was detected in mouse intestinal tissue (25). Taken together, these results lead to the conclusion that COX-2 is constitutively expressed in the mouse small intestine.…”
Section: Discussionsupporting
confidence: 80%
“…Similar findings were reported in other recent studies investigating COX-2 expression in the mouse (25) and in porcine intestinal tissue (3). Furthermore, Murmu et al have demonstrated that not only the COX-2 protein band but also the mRNA for COX-2 was detected in mouse intestinal tissue (25). Taken together, these results lead to the conclusion that COX-2 is constitutively expressed in the mouse small intestine.…”
Section: Discussionsupporting
confidence: 80%
“…To account for this specificity and because the mRNAs targeted by radiation were found to be components of functional pathways and interactive networks the post-transcriptional operon model put forth by Keene and Tenenbaum (26), which hypothesizes that RNA-binding proteins regulate the translation of functionally related mRNAs, may be applicable. Along these lines, Murmu et al have reported that after whole body irradiation the RNA-binding protein CUGBP2 is induced in the mouse intestine, which was proposed to regulate cyclooxygenase-2 translation (27). In addition, epidermal growth factor receptor stimulation, which can occur after irradiation (25), was shown to result in the phosphorylation of CUGBP1 and increase its activity in mammary epithelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…The 3Ј-untranslated region of COX-2 mRNA contains multiple copies of adenylate-and uridylate-rich elements that can be bound by proteins to alter COX-2 mRNA stability and translation (80). Proteins that interact with the COX-2 adenylate-and uridylate-rich element to modulate protein expression include the ELAV (embryonic lethal abnormal vision) protein HuR (84 -87), CUG triplet repeat-binding protein 2 (CUGBP2) (84,88,89), and T-cellrestricted intracellular antigen-1 (TIA-1) (82,87). It is intriguing to speculate that the AhR may regulate the expression and/or function of one or more of these proteins, thereby providing a new level of control for COX-2 protein expression.…”
Section: Fibroblasts Ahrmentioning
confidence: 99%